Extended optical/NIR observations of Type Iax supernova 2014dt: Possible signatures of a bound remnant. (8th December 2018) - Kawabata, Miho; Kawabata, Koji S; Maeda, Keiich; Yamanaka, Masayuki; Nakaoka, Tatsuya; Takaki, Katsutoshi; Fukushima, Daiki; Kojiguchi, Naoto; Masumoto, Kazunari; Matsumoto, Katsura; Akitaya, Hiroshi; Itoh, Ryosuke; et al.
Abstract: We present optical and near-infrared observations of the nearby Type Iax supernova (SN) 2014dt from 14 to 410 d after the maximum light. The velocities of the iron absorption lines in the early phase indicated that SN 2014dt showed slower expansion than the well-observed Type Iax SNe 2002cx, 2005hk, and 2012Z. In the late phase, the evolution of the light curve and that of the spectra were considerably slower. The spectral energy distribution kept roughly the same shape after ∼100 d, and the bolometric light curve flattened during the same period. These observations suggest the existence of an optically thick component that almost fully trapped the γ-ray energy from 56 Co decay. These findings are consistent with the predictions of the weak deflagration model, leaving a bound white dwarf remnant after the explosion.